Predictive performances of ALS and BLS termination of resuscitation rules in out-of-hospital cardiac arrest for different resuscitation protocols - Yu-Yuan Lin; Yin-Yu Lai; Hung-Chieh Chang; Chien-Hsin Lu; Po-Wei Chiu; Yuh-Shin Kuo; Shao-Peng Huang; Ying-Hsin Chang; Chih-Hao Lin (BMC Emergency Medicine, 2022)
Abstract Background Resuscitation guidance has advanced; however, the predictive performance of the termination of resuscitation (TOR) rule has not been validated for different resuscitation protocols published by the American Heart Association (AHA). Methods A retrospective study validating the basic life support (BLS) and advanced life support (ALS) TOR rules was conducted using an Utstein-style database in Tainan city, Taiwan. Adult patients with nontraumatic out-of-hospital cardiac arrests from January 1, 2015, to December 31, 2015, (using the AHA 2010 resuscitation protocol) and from January 1, 2020, to December 31, 2020, (using the AHA 2015 resuscitation protocol) were included. The characteristics of rule performance were calculated, including sensitivity, specificity, positive predictive value (PPV) and negative predictive value. Results Among 1260 eligible OHCA patients in 2015, 757 met the BLS TOR rule and 124 met the ALS TOR rule. The specificity and PPV for predicting unfavorable neurological outcomes were 61.1% and 99.0%, respectively, for the BLS TOR rule and 93.8% and 99.2%, respectively, for the ALS TOR rule. A total of 970 OHCA patients were enrolled in 2020, of whom 438 met the BLS TOR rule and 104 met the ALS TOR rule. The specificity and PPV for predicting unfavorable neurological outcomes were 85.7% and 100%, respectively, for the BLS TOR rule and 99.5% and 100%, respectively, for the ALS TOR rule. Conclusions Both the BLS and ALS TOR rules performed better when using the 2015 AHA resuscitation protocols compared to the 2010 protocols, with increased PPVs and decreased false-positive rates in predicting survival to discharge and good neurological outcomes at discharge. The BLS and ALS TOR rules can perform differently while the resuscitation protocols are updated. As the concepts and practices of resuscitation progress, the BLS and ALS TOR rules should be evaluated and validated accordingly.